Acute Dengue Hemorrhagic Encephalitis in a Child: A Case Report - Jagadishkumar, Kalenahalli (J Pediatr Neurosci, 2020)
Expanded dengue syndrome includes unusual or atypical manifestations of dengue fever by involving various organ systems. There have been increasing reports of dengue fever with unusual manifestations. Even though dengue virus is considered as a non-neurotropic virus, central nervous system complications have been reported. We are reporting a 4-year-old child who presented with acute dengue hemorrhagic encephalitis along with classical features of dengue infection and magnetic resonance imaging findings, suggestive of hemorrhage in the thalamus and cerebellum.